An update of the distribution of the assassin bug Zelus renardii (Heteroptera: Reduviidae) in Chile, with first records from the Oceanic Easter Island - Faundez, Eduardo; Vargas, Catalina J.; Carvajal, Mariom A. (My University, 2023)
The distribution of Zelus renardii (Kolenati) in Chile is updated. The new records extend their distribution to both north and south extremes, from Arica y Parinacota to Magallanes regions. Additionally, first records are provided for the Oceanic Easter Island.
Keywords: faunistics; harpactorinae; invasive species; south america